Investigation of plasma states formed under the interaction of high-power laser pulses with wire-shape Al–Cu target. Issue 1 (February 2021) - Golovin, D O; Alkhimova, M A; Pikuz, T A; Abe, Y; Honoki, Y; Lee, S; Matsuo, K; Koga, K; Okamoto, K; Shokita, S; Arikawa, Y; Faenov, A Ya; et al.
Abstract: Study of warm dense matter remains a very important task for understanding of many unique phenomena observing as in astrophysical research as in inertial fusion and fast ignition. In this work, we studied the parameters of plasma created by 1.7 ps laser pulses of relativistic intensity of 7 × 10 18 W/cm 2 in a specially designed Al–Cu wire-shape target, in comparison with a flat Cu and Al foil targets. We observed the strong emission of neutral or virtually neutral Cu Kα line from both Cu foil and Cu wire part of targets, which indicates the creation of a dense state exposed to the intense flow of hot electrons. Parameters of the plasma were evaluated by comparison of experimental spectra with the results of modeling by collisional-radiative kinetic code PrismSpec under the plasma zone approach. The using of Al foil in front of Cu wire part of target allowed avoiding the direct heating of Cu-wire and acquiring spectra of Cu K-shell emission evidently belonging to emission of warm dense matter (WDM) state. The upper estimate for the electron temperature in WDM region was found to be below 80 eV.